P153 Assessing the utility of the EUROLINE® testing system to screen for myositis/ILD-associated autoantibodies in patients with an ILD MDT consensus diagnosis of IPF. (December 2018) - Benson, RM; Lyon, M; Cotton, CV; Tate, R; Judge, EP; Cooper, RG; Spencer, LG
Abstract : Background: Differentiating CTD-ILD from IPF can be very difficult, because of overlapping HRCT and lung biopsy patterns, and subtle CTD clinical features. Autoantibody testing can raise awareness of the presence of a covert CTD. CTD-ILD associated with amyopathic myositis is a particularly difficult group to diagnose. Anti-Jo-1 antibody testing is commonplace in ILD, but other myositis–associated antibodies, which also associate with CTD-ILD, are not routinely tested for. 1 Immunoprecipitation is the gold standard for autoantibody testing, but is expensive and of very limited availability. The EUROLINE testing system is a commercially available system that tests for 16 myositis-associated antibodies, 8 of which are also ILD-associated. Following introduction of EUROLINE testing into our clinical practice, we assess here its utility to exclude covert CTD-ILDs in an IPF cohort from our clinic. Methods: We analysed data from 151 consecutive patients to November 2016, diagnosed with IPF by ILD MDT consensus at a UK ILD specialist center. Patient serology included the EUROLINE: Autoimmune Inflammatory Myopathies 16 Ag test (EUROIMMUN). All cases with positive EUROLINE results were also reviewed by a rheumatologist expert in EUROLINE interpretation. Results: A positive EUROLINE test was found in 35/151 (23%) of patients, table 1. Only 14/35 (40%) of the positive results were autoantibodies known to be associated with CTD-ILD. Following rheumatology review, all 35 positive results were deemed to be clearly false positives. Conclusions: EUROLINE identified false positives in a significant number of IPF cases, so, clinicians need to be cautious regarding the interpretation of this type of CTD-ILD screening. However, with care, myositis-ILD screening may have an important role to play in the evaluation of ILD/IPF cases. Many chest physicians will be unfamiliar with the use of this antibody panel for myositis-ILD screening, and we suggest that an expert rheumatology opinion is sought where positive results are obtained. This methodology could potentially lead to more accurate diagnoses and easier treatment choices. Only some of the EUROLINE antibody specificities are known to be ILD-associated, making it easier to identify many of the false positives as erroneous. Reference: Cotton CV, Spencer LG, New RP, Cooper RG. The utility of comprehensive autoantibody testing to differentiate connective tissue disease associated and idiopathic interstitial lung disease subgroup cases. Rheumatology2017;56:1264–71